Fusion Proteins Could Generate False Positives in Peptide Phage Display - Kishore K. Murthy; Irena Ekiel; Shi-Hsiang Shen; Denis Banville (BioTechniques)
Fusion proteins are frequently used in the functional characterization of newly discovered proteins and to identify interacting partners. In our study of hPTP1E, a cytosolic protein tyrosine phosphatase, we used glutathione S-transferase (GST)-fusion protein of the second PDZ domain to identify interacting peptide motifs by peptide phage display. A consensus motif G X X V W L G was identified and found to be specific for binding to GST-PDZ2 as determined by ELISA, peptide displacement and by protein overlay. However, using nuclear magnetic resonance (NMR), no interaction of the peptide was observed with PDZ2 alone. In co-precipitation experiments using the consensus peptide cross-linked to Affi-Gel®, only GST-PDZ2 (but not PDZ2 or GST alone) could be precipitated. These data suggest that there is a potential for identification of artifacts when using fusion proteins in peptide phage display, and one should exercise caution in interpreting these results. It is critical that the interaction be verified using a second, independent system.